The inspection of level crossing rails using guided waves. (10th August 2018) - Evans, Mark; Lucas, Andrew; Ingram, Ian
Highlights: Description of the costs and limitations of current inspection methods for level crossing rails. Introduction to Guided Wave Testing (GWT) for rails. Description of the applicability of this method to the inspection of level crossing rails. Practical experiences and results of trials by Network Rail. Abstract: Level crossing rails are high risk areas due to the combination of the limited effectiveness of current inspection methods and high corrosion rates which often exist. This paper discusses the current UK standard practices for the periodic inspection of level crossing rails using visual (VT) and conventional ultrasonic (UT) methods. The limitations of these methods are discussed and how these limitations affect the overall maintenance program for level crossings. A new inspection method, guided wave testing (GWT) is then described with particular emphasis on its advantages for inspecting level crossings. GWT was first commercially used for the inspection of pipes from around 1999 (Alleyne et al., 2001) [1] and has now gained very widespread usage. Finally, a review is given of the current Network Rail trial of GWT on level crossings using the G-Scan system, with representative results which demonstrate the effectiveness of GWT for this application.